Four from the forties : Arliss, Crabtree, Knowles and Huntington - McFarlane, Brian, 1934- (British film makers., 2018)
The 'Gainsborough melodramas' were a mainstay of 1940s British cinema, and helped make the careers of such stars as Margaret Lockwood, James Mason and Stewart Granger. But what was unique about these films? And who were the directors behind them? This book presents four key filmmakers, each with his own talents and specialities. It traces their professional lives through the highs of the 1940s, when the popularity of Gainsborough films was at its peak, to the tougher decades that followed the genre's decline. Featuring expert analysis of such films as The Man in Grey (1943), Madonna of the Seven Moons (1945) and The Upturned Glass (1947), alongside valuable historical context, the book constitutes the first extended examination of this group of directors. It combines critical acumen with readability, making it a valuable resource for students, lecturers and general readers alike.